(untitled) (Marketing Journal, 2025)
The article comprehensively analyzes the theoretical and practical aspects of managing and developing warehouse operations within the logistics system. The 330 importance of warehouses in production and service processes, as well as their functional role in the logistics chain, is scientifically substantiated. The study examines opportunities to increase resource utilization efficiency, reduce costs, and improve the quality of logistics services through the enhancement of warehouse activities. It describes ways to boost operational efficiency by integrating modern technologies, automation, and digital solutions into warehouse systems. Additionally, a scientific classification of warehouse types based on their role in the production process and the service sector is provided. The conclusion offers practical recommendations for modernizing warehouse services, introducing innovative technologies, and developing human capital.